Initial results and observations on a radiocarbon dating program in the Riverland region of South Australia. Issue 2 (3rd May 2020) - Westell, Craig; Roberts, Amy; Morrison, Mick; Jacobsen, Geraldine; ,
Abstract: This paper presents a preliminary occupation chronology for the Riverland region of South Australia, based on 31 radiocarbon age determinations. This region has represented a significant geographic gap in understanding occupation chronologies for the broader Murray-Darling Basin. The dating forms part of an ongoing research program exploring the long-term engagements of Aboriginal people with the habitat mosaics of the central River Murray corridor. Dating targets were selected on the basis of their landscape context. Results relate occupation evidence to an evolving riverine landscape through the period extending from approximately 29 ka to the late Holocene. These results include the first pre-Last Glacial Maximum ages returned on the River Murray in South Australia and extend the known Aboriginal occupation of the Riverland by approximately 22, 000 years.